Education, class and assortative marriage in rural Shanxi, China in the mid-twentieth century. (April 2020) - Xing, Long; Campbell, Cameron; Li, Xiangning; Noellert, Matthew; Lee, James
Abstract: This paper examines the consequences of political, economic and social change in mid-twentieth century China for patterns of assortative mating by both education and class. Traditionally in China, marriages were arranged by parents, and ideally matched families of similar socioeconomic status. However, the Marriage Law passed by the People's Republic of China in 1950 promoted free choice and forbade arranged marriage and other interference by families in the marriage decisions of their children. Later, Land Reform, Collectivization and other movements had profound impacts on rural household organization and social relations. We investigate their effects on assortative mating by using novel linked administrative data compiled in rural Shanxi Province in North China in the mid-1960s. These data record the education and family class labels ( jiating chushen ) of spouses for 1459 couples in 30 villages. The class labels were assigned in the 1950s based on family landholding before the Land Reform and became hereditary. We find that class label had effects above and beyond those of education, suggesting that assortative mating studies that only consider education overlook an important dimension of social status in marriage patterns, and thereby overstate the overall permeability of boundaries between social groups. Furthermore, by comparing couples according to whether they married before or after 1949, we find that patterns of homogamy and hypergamy remained highly stable in the face of substantial social transformation after 1949.